Impact of remittances, foreign direct investment and gross capital formation on economic growth in Timor-Leste: Strategies for sustainable development - Anuno, Fernando; Reis, Cristovao dos; Jesus, Bia Carvalho; Céu, Feliciano Quintas do (Asian Journal of Economic Modelling, 2025)
Timor-Leste is highly dependent on oil, and diversification of productive sectors is essential for attracting foreign direct investment (FDI) and remittances as contributions to GDP. This study analyzes the impact of remittances, FDI, and gross capital formation (GCF) on economic growth in Timor-Leste, with a focus on sustainable development strategies. Using an autoregressive distributed lag (ARDL) model, the analysis investigates short- and long-term dynamics among these critical economic indicators: remittances, FDI, GCF, and GDP growth from 2006 to 2023. The findings indicate that while FDI exerts a negative long-term impact on GDP, it plays a positive role in the short term. In contrast, GCF significantly increases economic growth in the long term. However, remittances do not have a significant impact on GDP in either the short or long term. Furthermore, Granger causality tests confirm that FDI significantly predicts GDP growth, emphasizing its crucial role in the economic development of Timor-Leste. Based on these insights, this study outlines strategic policy recommendations to enhance the effectiveness of FDI and capital formation in driving sustainable economic growth. These suggestions include targeted policies to boost FDI inflows and strengthen GCF, such as improving infrastructure, strengthening institutional frameworks, and promoting diversification of key sectors. By aligning investment strategies with the Sustainable Development Goals, Timor-Leste can reduce its reliance on oil and achieve more robust economic growth. These insights provide valuable guidance to policymakers and decision-makers seeking to leverage FDI and capital formation for long-term prosperity.